2019
DOI: 10.3390/colloids3040061
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Mesoporous NaZrP Cation-Exchanger for U(VI) Ions Separation from Uranyl Leach Liquors

Abstract: As the demand for uranium production-based energy worldwide has been increasing in the last decades to maintain nuclear growth for electricity production, there are great efforts towards developing an easy and inexpensive method for uranium extraction and separation from its ores. For this purpose, mesoporous inorganic cation exchangers provide an efficient separation technology that can help streamline production and lower overall cost. This study describes the development of nano-structured mesoporous sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Furthermore, the complexation strength between the DPTS and uranyl ions was found to increase at higher pH, which is another reason for the pH-dependent U(VI) sorption into SiO 2 -DPTS pores. Uranium can be hydrolyzed into different mononuclear and polynuclear hydrolyzed species in the form of [(UO 2 )m (OH) n ] (2m-n)+ [28]. At low pH values, the primary speciation of U(VI) ions in the solution is UO 2 2+ .…”
Section: Uranium Adsorptionmentioning
confidence: 99%
“…Furthermore, the complexation strength between the DPTS and uranyl ions was found to increase at higher pH, which is another reason for the pH-dependent U(VI) sorption into SiO 2 -DPTS pores. Uranium can be hydrolyzed into different mononuclear and polynuclear hydrolyzed species in the form of [(UO 2 )m (OH) n ] (2m-n)+ [28]. At low pH values, the primary speciation of U(VI) ions in the solution is UO 2 2+ .…”
Section: Uranium Adsorptionmentioning
confidence: 99%
“…Several methods have been used or suggested to remove uranium and other heavy metal ions from a nuclear waste solution, such as chemical precipitation, adsorption, membrane ltration, and ion exchange. [7][8][9][10][11][12][13][14] However, photocatalytic degradation is receiving increasing interest for removing radionuclide complexes from contaminated solutions due to the low cost of operation, simplicity, and environmental friendliness. [15][16][17][18][19] Recent work has revealed that photo-generated electrons can convert uranium into an insoluble form to reduce the soluble hexavalent state to its insoluble quaternary state.…”
Section: Introductionmentioning
confidence: 99%
“…They examined the crystal structure and characteristics of their colour optical properties in the visible spectrum (400 to 700 nm) for pigment application. In addition, nano-structured mesoporous sodium zirconium phosphate was fabricated and characterised for separation and extraction of uranyl ions from real samples [19,20]. Furthermore, Eu 2+ doped A 0.5 Zr 2 (PO 4 ) 3 (A = Ca, Sr, Ba) phosphors were synthesized by a co-precipitation method [16].…”
Section: Introductionmentioning
confidence: 99%